The Challenge of Implementing Corporate Social Responsibility in Sustainability Certified Palm Oil Mills (Case Study PT X and PT Y) - Winarti, Rachel Yessica; Siagian, Yolanda Masnita; Utha, Maria Ariesta (Devotion : Journal of Research and Community Service, 2023)
CSR is the company's responsibility for the impact of its activities and decisions on society and the environment. Implementation of CSR guided by the principles of ISO 26000 can optimize CSR efforts in the company. CSR has an important role in improving people's welfare and reducing environmental impact, but the implementation of CSR is still not optimal. This shows that palm oil mills need to make improvement efforts so that CSR implementation becomes more optimal, the research aims to determine the challenges in implementing CSR programs and provide recommendations to overcome dominant challenges. This research used delphi methods to assess the relevance of challenge and TOPSIS methods for prioritize the challenge. The first step in formulating improvement efforts is identifying the challenging factors in CSR implementation. The Delphi method aims to assess the relevance of challenges; the Delphi results show one additional challenge: "The emergence of the latest laws and regulations that cause significant changes to existing operations". Sixteen challenges become input in the TOPSIS method. The TOPSIS calculation results show three main challenges in this study. These three challenges include (1) Factor A5, "Company coordination with stakeholders (government, local communities, society, NGOs) is not good” 0.659984), (2) Factor E5 "The company's regulatory structure is complex in supporting the implementation of CSR programs" (0.596638), and (3) Factor D2 "Lack of certainty of economic benefits from technology investment initiatives that support CSR programs" (0.586047). This research showed that coordination between stakeholders is the most challenging factor when a company implements CSR programs. A recommendation in line with ISO 26000 is implementing a stakeholder engagement strategy through discussion forums. Regular communication forums will strengthen collaboration between stakeholders and will facilitate the society or local community in voicing the need for the program to be funded by the company.